Optimal Control Mathematical Model of Covid-19 With Social Distancing and Therapy Effect Strategies - Dwi Meldya Lestari; Kasbawati Kasbawati (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2022)
This article presents the mathematical modeling of covid-19 spread with optimal control that aims to observe the dynamics with social distancing and therapeutic effect. We use two control functions, namely  to minimize the susceptibility to move to the carrier population and  to maximize the severe symptom to move to the recovery population. Numerical solution using the forward-backward sweep method with Runge Kutta 4th order, numerical simulation on the optimal control problem. The simulation results obtained are the best strategy for controlling COVID-19 disease.